On two Liphistius species (Araneae: Liphistiidae) from Laos - Schwendinger, Peter J. (Zootaxa, 2013)
Two mesothelid trapdoor spider species, Liphistius isan Schwendinger, 1998 and L. laoticus sp. n., are reported from southern Laos, east of the Mekong River. Liphistius isan was previously known only from the type locality in northeastern Thailand, and it is here also reported from a second Thai locality. Liphistius laoticus sp. n. is newly described from males and females. The two species belong to distinct lineages and they both have their closest relatives in northeastern Thailand. Information on biology and relationships of these two species is given.